Occurrence of acrylamide, hydroxymethylfurfural and furaldehyde as process contaminants in traditional breakfast cereals: "Bsissa". (June 2021) - Ghazouani, Tesnime; Atzei, Alessandro; Talbi, Wafa; Fenu, Maurizio Antonio; Tuberoso, Carlo; Fattouch, Sami
Abstract: Hydroxymethylfurfural (HMF), furaldehyde (FAL) and acrylamide (AA) are produced during the food roasting process. The content of these toxic products in a common ready-to-eat breakfast, known as "Bsissa", was investigated. This North African traditional food is mainly based on roasted cereals, leguminous and spices. In the present study, thirty-four commercial "Bsissa" have been investigated for their toxic HMF, FAL and AA content using RP-HPLC-DAD. Additionally, to distinguish the main way of the production of these toxic products (Maillard reaction or caramelization origin), total protein, carbohydrates and reducing sugar were quantified and found in the range 5.63–25.72 g, 45.75–84.33 g and 0.37–3.74 g per 100 g of Bsissa, respectively. This result makes it also suitable to cover daily needs as a breakfast food. Obtained results showed that HMF and FAL were detected in most samples, with values not exceeding 24.71 mg/100 g and to 3.91 mg/100 g, respectively. AA was not detected in all the studied samples. Principal components (PC) and hierarchical classification were employed to establish the samples' heat damage based on relations between variables. Two PCs were obtained which explain more than 75% of the total variance, thus grouping the Bsissa in two clusters based on the main used cereal. This analysis may help in the mitigation step of furanic compounds by choosing the appropriate Bsissa ingredients. Highlights: Acrylamide, HMF and furaldehyde were evaluated in 34 traditional breakfast cereal. Bsissa is a good source of protein and carbohydrate and is a healthy breakfast. No detection of acrylamide level in all Bsissa samples. The HMF and furaldehyde are found under the daily intake fixed by researchers.